Dynamic increase in myoglobin level is associated with poor prognosis in critically ill patients: a retrospective cohort study - Liu, Yishan; Jiang, Jinlong; Yuan, Hao; Wang, Luhao; Song, Wenliang; Pei, Fei; Si, Xiang; Miao, Shumin; Chen, Minying; Gu, Bin; Guan, Xiangdong; Wu, Jianfeng (Frontiers in Medicine, 2024)
Background: Myoglobin is an important biomarker for monitoring critically ill patients. However,the relationship between its dynamic changes and prognosis remains unclear.Methods: We retrospectively enrolled 11,218 critically ill patients from a general and surgical intensive care unit of a tertiary hospital between June 2016 and May 2020.Patients with acute cardiovascular events, cardiac and major vascular surgeries, and rhabdomyolysis were excluded.To investigate the early myoglobin distribution, the critically ill patients were stratified according to the highest myoglobin level within 48 hours after ICU admission. The critically ill patients with more than three measurements within 1 week after ICU admission were included, and latent class trajectory modeling was used to classify the patients. The characteristics and outcomes were compared among groups.Sensitivity analysis was performed to exclude patients who had died within 72 hours after ICU admission. Restricted mean survival time regression model based on pseudo values was used to determine the 28-day relative changes in survival time among latent classes.The primary outcome was evaluated with comparison of in-hospital mortality among each Trajectory group, and the secondary outcome was 28-day mortality.Results: Of 6,872 critically ill patients, 3,886 (56.5%) had an elevated myoglobin level (≥150 ng/mL) at admission to ICU, and the in-hospital mortality significantly increased when myoglobin level exceeded 1,000 µg/mL. In LCTM, 2,448 patients were independently divided into four groups, including the steady group (n=1,606, 65.6%), the gradually decreasing group (n=523, 21.4%), the slowly rising group (n=272, 11.1%), and the rapidly rising group (n=47, 1.9%). The rapidly rising group had the largest proportion of sepsis (59.6%), the highest median Sequential Organ Failure Assessment score (10), and the highest in-hospital mortality (74.5%).Sensitivity analysis confirmed that 98.2% of the patients were classified into the same group as in the original model.Compared with the steady group, the rapidly rising group and the slowly rising group were significantly related to the reduction in 28-day survival time (β=−12.08; 95% CI −15.30 to −8.86; β=−4.25, 95% CI −5.54 to −2.97).Conclusion: Elevated myoglobin level is common in critically ill patients admitted to the ICU. Dynamic monitoring of myoglobin levels offers benefit for the prognosis assessment of critically ill patients.